Factors Associated with Favorable Tuberculosis Treatment Outcomes Determined Using Multiple Regression Analysis in Lusaka, Zambia, 2022 - Samuel Daka; Masaki Ota; Graham K Samungole (International Journal of Mycobacteriology)
Background: This study aims to identify the factors associated with favorable treatment outcomes of tuberculosis (TB) patients registered at two hospitals and two urban health centers in Lusaka, Zambia in 2022. Methods: A retrospective cohort study was conducted, focusing on patients who were either cured or completed treatment, defined as having favorable treatment outcomes. Unfavorable treatment outcomes included treatment failure, death, lost to follow-up, or not evaluated. Results: A total of 2945 patients were registered, of whom, 2071 (70.3%) were males and 1346 (45.7%) were bacteriologically confirmed cases. The overall treatment success rate across the facilities was 88.2%. Multiple regression analysis revealed that patients with contact details were 2.16 (95% confidence interval [CI]: 1.30–3.61) times more likely to achieve favorable treatment outcomes compared to those without. Conversely, for each year of increasing age, the likelihood of favorable outcomes decreased by 0.99 (95% CI: 0.98–1.00) times. Patients with unknown HIV status were 0.0079 (95% CI: 0.0024–0.0259) times more likely to have favorable outcomes compared to those who were HIV negative. In addition, patients treated at Facilities A and B had 4.8 (95% CI: 2.7–8.4) and 1.8 times (95% CI: 1.1–3.0), respectively, higher odds of favorable outcomes than those at Facility D. Conclusion: Healthcare providers should prioritize collecting contact details and testing HIV, especially in older adults with presumptive TB. Early diagnosis and proactive management strategies are essential for improving treatment outcomes.